HGF/R-spondin1 rescues liver dysfunction through the induction of Lgr5+ liver stem cells. Issue 1 (December 2017) - Lin, Yuan; Fang, Zhe-Ping; Liu, Hong-Juan; Wang, Li-Jing; Cheng, Zhiqiang; Tang, Na; Li, Tingting; Liu, Tengfei; Han, Hai-Xiong; Cao, Guangwen; Liang, Li; Ding, Yan-Qing; et al.
Abstract Induction of endogenous adult stem cells by administering soluble molecules provides an advantageous approach for tissue damage repair, which could be a clinically applicable and cost-effective alternative to transplantation of embryonic or pluripotent stem cell-derived tissues for the treatment of acute organ failures. Here, we show that HGF/Rspo1 induce liver stem cells and rescue liver dysfunction. Carbon tetrachloride treatment promotes both fibrosis and Lgr5+ liver stem cell proliferation, whereas Lgr5 knockdown worsens fibrosis. Injection of HGF in combination with Rspo1 increases the number of Lgr5+ liver stem cells and improves liver function by attenuating fibrosis. We observe Lgr5+ liver stem cells in human liver fibrosis tissues, and once they are isolated, these cells are able to form organoids, and treatment with HGF/Rspo1 promotes their expansion. We suggest that Lgr5+ liver stem cells represent a valuable target for liver damage treatment, and that HGF/Rspo1 can be used to promote liver stem cell expansion. Organ regeneration by transplantation of ESC/iPSC-derived tissues is a promising but still challenging approach. Here Lin et al. show that liver damage caused by a chemical insult induces not only fibrosis but also Lgr5+ cell expansion that can be further promoted by treatment with HGF/R-spondin1.